Ileovesicostomy Update: Changes for the 21st Century - W. Britt Zimmerman; Richard A. Santucci (Advances in Urology)
Objectives. To review the literature regarding ileovesicostomy and evaluate our patient population for clinical characteristics. Methods. Various surgical reconstructive techniques allow management of difficult clinical scenarios involving patients with neurogenic bladder, irretraceable lower urinary tract symptoms, lower urinary tract disaster, and urethrocutaneous fistulae. One such reconstructive technique employed is the ileovesicostomy. This procedure provides patients with a low-pressure urinary conduit utilizing the ileum and native bladder that empties without catheterization. We describe our patient population who underwent ileovesicostomy for 5 consecutive years ending 2007 at Detroit Receiving Hospital. Results. Most common diagnosis was neurogenic bladder secondary to spinal cord injury. Our population and clinical outcomes are similar to those previously reported in the literature. Conclusions. Based on our experience, we suggest that patients with severe lower urinary tract symptoms and who are unable to perform clean intermittent catheterization and/or refractory to medical therapy ileovesicostomy should be the procedure of choice.